PUBLIC ADMINISTRATION OF MEMBER STATES UNDER THE CONTROL OF THE EUROPEAN UNION - A. Boros (Сравнительная политика)
This paper seeks to find out how the European Union operates from an administrative point of view and what set of tools has become necessary to implement the policy objectives of the European Union. The first part of the paper presents the specific features of the European Union in relation to the Member State administrative systems, and what the common organizing principles are that ensure the functioning. In the two-tier administrative system, the Commission should provide for the proper application and implementation of the Treaties and other measures. However, the actual implementers thereof are mostly the Member States, therefore, the administrative bodies are of special importance in actually enforcing EU law at local and member state level. The EU needs different tools in order to operate this huge mechanism. The first part of our study intends to present this set of tools, in this context, the infringement procedure, the complaint procedures and petition cases that can be initiated by EU citizens and businesses, and the so-called other problem-solving tools such as SOLVIT or the European Consumer Centres Network will also be analysed. The second part of the study deals with the way of EU implementation, i.e. the EU administrative procedure: the complex EU administrative system currently operates under heterogeneous procedural rules and there is no uniform procedural law. Given the a priori complex EU administrative structure and the diverse regulatory environment, it is not surprising that the demand for changes and unification has emerged in this area in recent years. The second part of the study presents the objectives and challenges of this task. The third part of the study summarizes the area covered within the framework of the compilation and makes proposals on the relevant issues of the Member States’ administrative systems affecting the European Union.